Bio-oil Production from Ablative Pyrolysis of Corncob Pellets in a Rotating Blade Reactor - N. Khuenkaeo (2018)
© Published under licence by IOP Publishing Ltd. Fast pyrolysis serves as an alternative and eco-friendly method to convert biomass into valuable bio-oil and char. Bio-oil is a potential source for generating renewable biofuels. In this study, corncob pellets were pyrolysed in a laboratory rotating blade ablative pyrolysis reactor. Effects of plate temperature (450 - 550°C) and nitrogen flowrate (5 - 15 L/min) were investigated on pyrolysis product yields at a fixed rotating speed of 6 Hz. Temperature and inert gas flowrate were shown to affect product distribution and yields. Maximum bio-oil yields of almost 50% w/w on dry basis were obtained at 550°C and flowrate of 5 L/min. Composition of the bio-oil contained predominantly oxygenated hydrocarbons. From analysis of chemical and physical properties, the bio-oil derived from corncob pellets showed good fuel quality, comparable to those bio-oils reported in the literature.